2022
DOI: 10.55976/dt.1202216523-36
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of breast cancer brain metastases: radiotherapy and emerging preclinical approaches

Abstract: The breast is one of the common primary sites of brain metastases (BM). Radiotherapy for BM from breast cancer may include whole brain radiation therapy (WBRT), stereotactic radiosurgery (SRS), and stereotactic radiotherapy (SRT), but a consensus is difficult to reach because of the wide and varied protocols, indications, and outcomes of these interventions. Overall, dissemination of disease, patient functional status, and tumor size are all important factors in the decision of treatment with WBRT or SRS. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 114 publications
0
9
0
1
Order By: Relevance
“…In studies that have demonstrated improved efficacy in patients with brain metastases, the majority include whole-brain radiotherapy (when multiple brain metastases are present) or local radiotherapy [stereotactic radiosurgery (SRS) when one or two brain metastases are present] in their treatment regimens to disrupt the blood-brain barrier, allowing Pyrotinib to reach the brain metastases. These treatments provide favorable clinical practice evidence for radiation therapy for brain metastases from breast cancer (32). After transtuzumab/T-DM1 or lapatinib therapy, it continues to work effectively, implying that Pyrotinib has the potential to reverse HER2 resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have demonstrated improved efficacy in patients with brain metastases, the majority include whole-brain radiotherapy (when multiple brain metastases are present) or local radiotherapy [stereotactic radiosurgery (SRS) when one or two brain metastases are present] in their treatment regimens to disrupt the blood-brain barrier, allowing Pyrotinib to reach the brain metastases. These treatments provide favorable clinical practice evidence for radiation therapy for brain metastases from breast cancer (32). After transtuzumab/T-DM1 or lapatinib therapy, it continues to work effectively, implying that Pyrotinib has the potential to reverse HER2 resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surgery, chemotherapy, radiotherapy, targeted therapy and immunotherapy are the main treatment strategies for cancers [20][21][22]. However, these methods still couldn't cure most of the human malignancies, especially the metastatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Local treatment for BM includes surgery, WBRT, SRS, fractionated stereotactic radiotherapy (fSRT), or a combination of these [ 6 , 22 ]. The decision of choosing one over another may be based on the estimated prognosis and the goals of the treatment [ 23 ].…”
Section: Local Treatment For Bmmentioning
confidence: 99%